Racial Disparity in Postpartum Readmission due to Hypertension among Women with Pregnancy-Associated Hypertension - Chornock, Rebecca; Iqbal, Sara N.; Kawakita, Tetsuya (American Journal of Perinatology, 2020)
Objective Postpartum hypertension is a leading cause of readmission in the postpartum period. We aimed to examine the prevalence of racial/ethnic differences in postpartum readmission due to hypertension in women with antepartum pregnancy-associated hypertension.Study Design This was a multi-institutional retrospective cohort study of all women with antepartum pregnancy-associated hypertension diagnosed prior to initial discharge from January 2009 to December 2016. Antepartum pregnancy-associated hypertension, such as gestational hypertension, preeclampsia (with or without severe features), hemolysis, elevated liver enzyme, low platelet (HELLP) syndrome, and eclampsia was diagnosed based on American College of Obstetricians and Gynecologists Task Force definitions. Women with chronic hypertension and superimposed preeclampsia were excluded. Our primary outcome was postpartum readmission defined as a readmission due to severe hypertension within 6 weeks of postpartum. Risk factors including maternal age, gestational age at admission, insurance, race/ethnicity (self-reported), type of antepartum pregnancy-associated hypertension, marital status, body mass index (kg/m2), diabetes (gestational or pregestational), use of antihypertensive medications, mode of delivery, and postpartum day 1 systolic blood pressure levels were examined. Multivariable logistic regression models were performed to calculate adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs).Results Of 4,317 women with pregnancy-associated hypertension before initial discharge, 66 (1.5%) had postpartum readmission due to hypertension. Risk factors associated with postpartum readmission due to hypertension included older maternal age (aOR = 1.44; 95% CI: 1.20–1.73 for every 5 year increase) and non-Hispanic black race (aOR = 2.12; 95% CI: 1.16–3.87).Conclusion In women with pregnancy-associated hypertension before initial discharge, non-Hispanic black women were at increased odds of postpartum readmission due to hypertension compared with non-Hispanic white women.
Keywords: postpartum; preeclampsia; readmission